Clinical efficacy and immune effects of acupuncture in patients with comorbid chronic pain and major depression disorder: A double-blinded, randomized controlled crossover study - Liao, Hsien-Yin; Satyanarayanan, Senthil Kumaran; Lin, Yi-Wen; Su, Kuan-Pin (Brain, behavior, and immunity, 2023)
•Pain- or depression-specific acupoints improves chronic pain and depression, respectively.•Pain specific acupoints were hypothesized to reduce pain more than depression specific acupoints.•Pain-specific acupoints did not significantly reduce pain scale scores.•Depression-specific acupoints did not significantly reduce depression scales scores.•Immune effects of pain- or depression-specific acupoints confirm their effectiveness. Depression and pain are highly comorbid and share biological mechanisms. Acupuncture is commonly used to manage both pain and depression, but the choice of acupoints for specific disorders differs. This study aimed to investigate whether specific acupuncture intervention on pain- and depression-acupoints would have specific efficacy and immune effects in patients with comorbid chronic pain and major depressive disorder (MDD). We performed a subject- and assessor-blinded, crossover, and randomized controlled clinical trial of depression- and pain-specific acupuncture intervention and measured clinical responses and proinflammatory cytokines in patients with comorbid chronic pain and MDD. Specific acupoints for pain and depression were used in random order with a washout interval. Forty-seven patients were enrolled and randomly assigned to two groups: (1) the depression–pain group (23 patients who were treated with depression-specific acupoints and then the pain-specific acupoints after the washout) and (2) pain–depression group (24 patients with the reverse order). The pain-specific acupoints for pain did not reduce Brief Pain Inventory scores to a significantly greater degree (-0.97 ± 1.69) than the depression-specific acupoints (-0.28 ± 1.88); likewise, the depression-specific acupoints did not significantly ameliorate Hamilton Depression Rating Scale (-4.59 ± 6.02) than the pain-specific acupoints (-6.69 ± 6.61). The pain-specific acupoints improved Beck Depression Inventory-Second Edition (-6.74 ± 9.76) even better than the depression-specific acupoints (-1.92 ± 10.74). The depression-specific acupoints did not significantly decrease the depression-related interleukin (IL)-6 level (-1.24 ± 6.67) than the pain-specific acupoints (-0.60 ± 4.36). The changed levels of IL-1β, tumor necrosis factor (TNF)-α between the depression-specific acupoints (-37.41 ± 194.49; −12.53 ± 54.68) and the pain-specific acupoints (-15.46 ± 87.56; −7.28 ± 27.86) could not reach significantly different, too. This study rejected our hypothesis that the pain-specific acupoints might produce superior analgesic effects than the depression-specific acupoints and vice versa. The cytokine results might imply that pain and depression share common biological mechanisms. (trial registration: https://www.clinicaltrials.gov: NCT03328819).